An Interactive Study Between Green Marketing and the Competitive Capabilities of Electronic Banking Services Institutions in Iraq - Hassan Daghwi Obaid (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This interactive study examines the impact of green marketing on the development of competitive capabilities in Iraqi companies, highlighting its role as a strategic approach for achieving sustainable market advantage. Green marketing involves environmentally responsible practices in product design, pricing, promotion, and distribution, which contribute to building brand reputation and operational excellence. The study explores the relationship between green marketing initiatives and enhancing firms' competitive capabilities, emphasizing how eco-friendly practices influence performance and strategic positioning. By analyzing green marketing theory, the study provides a comprehensive understanding of how sustainability-focused strategies can strengthen innovation, differentiation, and customer loyalty. It underscores the role of green marketing in improving long-term competitiveness and aligning business goals with environmental responsibility. Using empirical studies and diverse sources, the research demonstrates that green marketing is not merely a branding tool but a core element in building strategic advantages, especially within Iraq’s evolving market and regulatory environment. The findings reveal a positive relationship between green marketing practices and competitive capabilities. Environmentally driven strategies improve firm performance, enhance responsiveness to market demands, and reinforce brand value, enabling companies to thrive in dynamic business contexts. Consequently, the research recommends adopting green marketing as an integral component of strategic planning for Iraqi companies to ensure resilience, sustainability, and competitive growth. In conclusion, the study highlights the positive impact of green marketing on enhancing competitive capabilities in the Iraqi context, affirming its importance as a foundational pillar in business strategy to address environmental challenges and achieve long-term success. Furthermore, it suggests future studies explore the specific challenges and opportunities of implementing green marketing in different sectors.